Prevalence and Predictors of Pediatric COVID-19 Vaccine Acceptance - Bourque, Stephanie L.; Weikel, Blair W.; Palmer, Claire; Cataldi, Jessica R.; Blackwell, Sarah; Hwang, Sunah S. (American Journal of Perinatology, 2022)
Objective As pediatric COVID-19 vaccine eligibility expands, understanding predictors of vaccine intent is critical to effectively address parental concerns. Objectives included: (1) Evaluate maternal COVID-19 vaccine intent for child(ren) and associated predictors of stated intent; (2) Describe attitudes related to hypothetical vaccination policies; (3) Summarize themes associated with intention to vaccinate child(ren) for COVID-19.Study Design Mothers enrolled in Heath eMoms, a longitudinal survey project, were recruited for this electronic COVID-19 survey. Chi-square analysis was used to compare proportions of respondent characteristics based on vaccination intent. Population survey logistic regression was used for multivariable modeling to assess the independent association between vaccine intent and demographics.Results The response rate was 65.3% (n = 1884); 44.2% would choose vaccination, 20.3% would not choose vaccination, and 35.5% are unsure whether to have their child(ren) vaccinated for COVID-19. Black mothers (AOR 0.26, 95% CI 0.13, 0.54), respondents with less than high school education (AOR 0.26, 95% 0.12, 0.56) and those in rural areas (AOR 0.28, 95% CI 0.16, 0.48) were less likely to choose vaccination. Commonly cited reasons for vaccine hesitancy include the belief that the vaccine was not tested enough, is not safe, and there are concerns regarding its side effects.Conclusion Over 50% of respondents do not intend or are unsure about their intent to vaccinate their child(ren) for COVID-19 with variability noted by demographics. Opportunities exist for perinatal and pediatric providers to educate pregnant people, parents, and caregivers with a focus on addressing concerns regarding vaccine safety and efficacy.Key Points
Keywords: COVID-19; vaccine hesitancy; vaccine acceptance